2022
DOI: 10.3390/antibiotics11091265
|View full text |Cite
|
Sign up to set email alerts
|

The Feed Additive Potassium Diformate Prevents Salmonella enterica Serovar Pullorum Infection and Affects Intestinal Flora in Chickens

Abstract: Extensive studies have shown that potassium diformate (KDF), an antibiotic substitute used as a feed additive, improves animal growth performance, although there is less direct evidence of its preventive effect on bacterial infections and its influence on the intestinal flora of animals. In this study, the inhibition effect of KDF on Salmonella enterica serovar Pullorum, an important enteric pathogen causing pullorum disease, was investigated in vitro and on a chicken infection model. The effect of KDF on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 59 publications
2
9
0
Order By: Relevance
“…The relative abundance of Bacteroides was significantly decreased and Ruminococcus_torques_group was significantly increased in the 23L:1D group, compared with the 12L:12D group ( P < 0.05). As the most common and abundant members of the gut microbiota, Bacteroides have long been considered as symbiotic colonizers, playing roles in maintaining intestinal homeostasis, anti-inflammation, and resisting intestinal pathogens ( Sun et al, 2022 ). In chickens, the supplementation of potassium diformate promoted the colonization of several probiotics, such as Bacteroides, Blautia, and Faecalibacterium , which are participate in regulation of inflammation and maintenance of the intestinal barrier ( Sun et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative abundance of Bacteroides was significantly decreased and Ruminococcus_torques_group was significantly increased in the 23L:1D group, compared with the 12L:12D group ( P < 0.05). As the most common and abundant members of the gut microbiota, Bacteroides have long been considered as symbiotic colonizers, playing roles in maintaining intestinal homeostasis, anti-inflammation, and resisting intestinal pathogens ( Sun et al, 2022 ). In chickens, the supplementation of potassium diformate promoted the colonization of several probiotics, such as Bacteroides, Blautia, and Faecalibacterium , which are participate in regulation of inflammation and maintenance of the intestinal barrier ( Sun et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…As the most common and abundant members of the gut microbiota, Bacteroides have long been considered as symbiotic colonizers, playing roles in maintaining intestinal homeostasis, anti-inflammation, and resisting intestinal pathogens ( Sun et al, 2022 ). In chickens, the supplementation of potassium diformate promoted the colonization of several probiotics, such as Bacteroides, Blautia, and Faecalibacterium , which are participate in regulation of inflammation and maintenance of the intestinal barrier ( Sun et al, 2022 ). In our laboratory, previous studies have found that an increase in the relative abundance of Ruminococcus_torques_group in the intestine is involved in tracheal inflammatory injury ( Zhou et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Adding KDF to the feed is a preventive alternative for maintaining the health of farmed fish. This can lower the intestinal pH [62], suppress the growth of pathogenic bacteria, mainly Gram-negative bacteria, aid in nutrient digestion and absorption, and have beneficial effects on animals' production performance [19]. KDF enhances the feed performance.…”
Section: Reducing Intestinal Ph Levelsmentioning
confidence: 99%
“…Attempts at control of FT should focus on prompt removal of affected birds and biosecure disposal of carcasses [6]. Experimentally, organic acids in feed or water appear to suppress mortality and reduce intestinal colonisation of chicks following oral inoculation of SP [26][27][28] or SG [29,30], or exposure to SG seeder birds [31]. However, at present corresponding field studies are not reported.…”
Section: Treatment and Resistance Treatmentmentioning
confidence: 99%